ANALYSIS OF STRATEGYC AND SYNCHRONIZATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) COMPANY PROGRAMS BASED ON ISO 26000 Case Study: EMP Malacca Strait S.A S.A - Yoke Aphrodite Balia; Hoga Saragih (Sean Institute, 2023)
Corporate Social Responsibility (CSR) is commitment of Company in the Business Community to contribute development a sustainable economic is economic aspect, social aspect and environment aspect. This study aims to develop Corporate Social Responsibility (CSR) strategic formulation based on ISO 26000 on environmental and community involvement and development core subjects in oil and gas operation area EMP Malacca Strait S.A. The strategic formulation developed by management tools Strategic Factor Analysis Summary (SFAS) by firstly analyzing gap between implemented CSR program and ISO 26000 standard using Gap Analysis and involving social mapping information. The FSAS is a SWOT (Strength, Weakness, Opportunity and Threat) management tool that become as a reference in making strategic in CSR program. EMP Malacca based on oil and gas working area contract still has an operation period until next August 2020, but EMP Malacca Strait has been get extended approval the working area from ESDM and SKKMIGAS with scheme different technic from technics Cost Recovery scheme to become technic Gross Split scheme. Base on this condition I would like analyst their program activities in 5 years before until termination contract the work area contract EMP Malacca and Analyst too next 5 years with condition new technics Gross Split decrease their program activities in last 5 years due to budget allocation set by company.